Drivers and mechanisms contributing to excess warming in Europe during recent decades - Buwen Dong; Rowan T. Sutton (npj Climate and Atmospheric Science)
Abstract Over the period 1979-2022, European surface air temperatures warmed around three times as fast as the global mean temperatures in both winter and summer. Here we define “excess” European warming as the difference between the rate of European regional warming and the rate of global warming and investigate the causes. Using a simple observation-based method, we estimate that around 40% ± 39% (in winter) and 29% ± 10% (in summer) of excess European warming is “dynamical” - attributable to changes in atmospheric circulation. We show that the rate of European warming simulated in CMIP6 models compares well with the observations, but only because these models warm too fast in the global mean; excess European warming is underestimated, particularly in winter. The CMIP6 models simulate well the magnitude of the thermodynamic component of excess European warming since 1979 in both winter and summer, they suggest only a weak dynamical contribution in the multi-model mean. The models suggest greenhouse gas-induced warming made the largest contribution to excess thermodynamic warming in winter, whereas changes in anthropogenic aerosols made the largest contribution in summer. They also imply a substantially reduced future rate of excess European warming in summer. However, the failure of current models to simulate observed circulation trends (either as a forced response or as a combination of forced response and internal variability) also implies large uncertainty in future rates of European warming.